Effects of a Trans-Theoretical Model-Based Health Education Program on the Management of Cognitive Dysfunction in Older Adults With Mild Cognitive Impairment: Study Rationale and Protocol Design for a Randomized Controlled Trial - Liu, Xiaoshen; Wang, Lina; Tao, Hong; Ge, Chenxi; Zhen, Xueting; Sun, Xue; Wang, Simeng; Su, Liming (Frontiers in Psychiatry, 2021)
Introduction: Recent studies have confirmed that the management of cognitive dysfunction produces considerable positive effects in individuals with mild cognitive impairment (MCI), however, compliance with participation in various cognitive dysfunction management strategies remains scant in older adults with MCI. Health education programs can improve the level of knowledge of the disease effectively, though it remains unclear as to whether health education programs are sufficient to promote behavior changes of older adults with MCI in the community. Objective: The study aims to provide insight into the effect of a trans-theoretical Model (TTM)-based health education program on increasing knowledge about mild cognitive impairment (MCI), compliance in cognitive dysfunction management, and other cognition-related health outcomes (general cognitive function, sleep quality, depression symptoms, apathy symptoms) for older adults with MCI. Methods: This study is a single-blinded, randomized, prospective clinical trial. We will recruit 132 participants with MCI who will be randomly assigned to a TTM-based health education group and a standard health education group in a ratio of 1:1. The intervention group will receive a TTM-based health education program (1 session/week, 4–560 min/session for 8 weeks), while the control group will receive standard health education. Assessors blinded to participant allocation will conduct baseline, post-intervention, and 3-month follow-up assessments. Statistical analyses will consist of the Wilcoxon test, the Chi-square test, the T-test, and 2 (group) × 3 (time) ANOVA with a 5% cut-off for significance. Discussion: Supposing the TTM-based health education program will provide validated community-based cognitive dysfunction management strategies for older adults with MCI, this would be a feasible approach to improve the compliance of participation in cognitive dysfunction management and the cognition-related health outcomes. Clinical Trial Registration: ChiCTR1900028351. Registered on December 19, 2019. http://www.chictr.org.cn/edit.aspx?pid=47223&htm=4.